Neurological Images and the Predictors for Neurological Sequelae of Epidemic Herpangina/Hand-Foot-Mouth Disease with Encephalomyelitis - Tsai, Jeng-Dau; Kuo, Hung-Tsung; Chen, Shan-Ming; Lue, Ko-Huang; Sheu, Ji-Nan (Neuropediatrics, 2014)
Since 1998 in Taiwan, enterovirus (EV) 71 epidemics have caused encephalomyelitis and placed a significant burden on parents and physicians. In this study, we present clinical manifestations, magnetic resonance (MR) imaging findings, and neurological sequelae on epidemic EV-infected patients with encephalomyelitis. Of the 46 patients, 14 patients presented with neurological sequelae; of them, 3 patients suffered from complications of mental regression. Predictors of unfavorable neurological sequelae were myoclonic jerks (> 4 times/night) and pleocytosis (167/μL) of the cerebrospinal fluid (CSF). Results from viral culture and MR imaging indicated that positive identification of EV71 infection was associated significantly with lesions on MR imaging. Our results show that hand-foot-mouth disease carries a higher risk of encephalomyelitis and that frequent myoclonic jerks and pleocytosis of the CSF are risk factors for subsequent neurological sequelae. Positive identification of EV71 might be useful as a predictor of lesions in MR imaging.
Keywords: enterovirus 71; neurological images; predictors; neurological sequelae; Taiwan